2019
DOI: 10.1123/jsr.2017-0217
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early Physical Activity Compared to Early Physical Rest on Concussion Symptoms

Abstract: Clinical Scenario: Currently, rest following concussion serves as the keystone of concussion treatment, but substantial evidence to support it is lacking. Recent literature suggests that early physical activity may be beneficial in reducing concussion symptoms which may influence clinical recovery time. Clinical Question: Does early physical activity decrease postconcussion symptoms compared to physical rest following concussion? Summary of Key Findings: A total of 5 articles were included that examined sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…The protocols for SRC are changing and are supported by the current literature. 4,10,13,14,15 Schneider et al 4 found that a brief period of cognitive and physical rest is appropriate for most patients (24-48 h), followed by a postacute period (48 h until symptom free) in which patients should be encouraged to engage in gradual progressive physical activity. Although gradual progressive physical activity is now recommended by the literature, no studies have addressed the mode or intensity of that physical activity during the postacute period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocols for SRC are changing and are supported by the current literature. 4,10,13,14,15 Schneider et al 4 found that a brief period of cognitive and physical rest is appropriate for most patients (24-48 h), followed by a postacute period (48 h until symptom free) in which patients should be encouraged to engage in gradual progressive physical activity. Although gradual progressive physical activity is now recommended by the literature, no studies have addressed the mode or intensity of that physical activity during the postacute period.…”
Section: Discussionmentioning
confidence: 99%
“…9 While 24 to 48 hours of rest postinjury is recommended, patients can be encouraged to begin cognitive and physical activity that remains below the threshold of symptom exacerbation following this time period. 9 Lempke et al's 15 systematic review, which supports this recommendation, concluded that physical activity performed within 0 to 7 days postconcussion resulted in a 32% decline in multiple reported symptoms when compared with those who were prescribed strict rest. The authors also noted that the physical activity group experienced greater symptom resolution at day 7, while the rest group reported greater symptom severity at day 10.…”
mentioning
confidence: 95%
“…Auch im Follow-up [32] konnte innerhalb des Interventionszeitrahmens lediglich Teilnehmern der IG wieder für ihre Sportart die Freigabe erteilt werden. Diese Ergebnisse bestätigen die Annahme, dass sowohl eine frühzeitige physiotherapeutische Intervention als auch eine Intervention zu einem späteren Zeitpunkt deutlich stärker zur Erholung beitragen als Ruhe alleine [19,21,40]. Patienten, die in der ursprünglichen Studie durch die Intervention keine Symptomfreiheit erreichen konnten, erzielten auch mit dem später angewandten Ruheprotokoll keine signifikanten Verbesserungen und erhielten daher keine RTP-Freigabe [32].…”
Section: Zusammenfassung Der Ergebnisseunclassified
“…Somit ist ein umfassender Therapieansatz notwendig, um die Symptome eines Postconcussion syndrome adäquat behandeln zu können. Der bislang empfohlene Ansatz der vollständigen Ruhe bis zur Symptomfreiheit wird inzwischen neu bewertet [19][20][21]. Aufgrund der biomechanischen und neurophysiologischen Gewebebeeinflussung wird angenommen, dass manualtherapeutische Techniken bei Patienten mit persistierenden Symptomen nach SRC schmerzlindernd und funktionssteigernd wirken [16,[22][23][24].…”
Section: Introductionunclassified
“…9 An increasing amount of evidence shows that an active approach, contrary to earlier beliefs about a "wait and see approach", can improve outcomes and long term prognosis. [10][11][12] The international consensus statement on Concussion in Sports from 2016 in Berlin recommends a period of 24-48 hours of physical and cognitive rest after the initial trauma, followed by a progressively active rehabilitation. 13 It is well established that PCS patients can experience barriers towards physical and cognitive activity, with higher levels of cognitive exertion associated with longer duration of symptoms in some, 14 and that adequate management between rest and activity is a central yet complex part of the recovery process.…”
Section: Introductionmentioning
confidence: 99%